Influence of treatment with 3'-deoxyadenosine associated deoxycoformycin on hematological parameters and activity of adenosine deaminase in infected mice with Trypanosoma evansi - Dalla Rosa L. (2013)
This study aimed to verify the effect of 3'-deoxyadenosine and deoxycoformycin on hematologic parameters and adenosine deaminase (ADA) activity in plasma and brain of mice infected with Trypanosoma evansi. Seventy animals were divided into seven groups, which were divided into two subgroups each for sampling on days 4 and 8 post-infection (PI). The groups were composed of three uninfected groups (A-C), namely, not-treated (A), treated with 3'-deoxyadenosine (B), and treated with deoxycoformycin (C) and four infected groups, mice with T. evansi (D-G), namely, not-treated (D), treated with 3'-deoxyadenosine (E), treated with deoxycoformycin (F), and treated with a combination 3'-deoxyadenosine and deoxycoformycin (G). Hematological parameters and ADA activity were evaluated in plasma and brain. Animals in groups B and C exhibited a reduction in the levels of plasma total protein compared group A. Animals in groups D and F showed changes in the hematological parameters. The ADA activity significantly reduced in the animals of groups C, D, F and G. Mice in the group E presented increased ADA activity in plasma. Therefore, we conclude that the treatment interferes significantly in the hematologic parameters in mice infected with T. evansi. On the other hand, when the ADA inhibitor was used we observed a significant decrease in the values of hematocrit, total erythrocytes, and hemoglobin concentration. The deoxycoformycin was able to inhibit the ADA activity of parasite thus it may be one of the mechanisms of efficacy of this treatment. © 2013 Elsevier Inc.